2020
DOI: 10.3389/fnins.2020.615854
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between the Ventrolateral Preoptic Nucleus and the Tuberomammillary Nucleus in Regulating the Sleep-Wakefulness Cycle

Abstract: The ventrolateral preoptic nucleus (VLPO) in the anterior hypothalamus and the tuberomammillary nucleus (TMN) in the posterior hypothalamus are critical regions which involve the regulation of sleep-wakefulness flip-flop in the central nervous system. Most of the VLPO neurons are sleep-promoting neurons, which co-express γ-aminobutyric acid (GABA) and galanin, while TMN neurons express histamine (HA), a key wake-promoting neurotransmitter. Previous studies have shown that the two regions are innervated between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Almost all of them have at least moderate histaminergic fiber density, suggesting that they are suitable for more functional research on neural circuits. In particular, VLPO, one of the most important brain nuclei that control the activity of histaminergic neurons ( 59 , 60 ), is very worthy of further research on potential closed-loop projection mechanisms. Brain histamine seems to promote motor functions overall ( 34 ), but there are still some studies that have come to different conclusions ( 61 63 ), which may be due to the different roles histamine plays in motor function in different brain regions, including globus pallidus ( 64 ), medial septal nucleus ( 39 ), nucleus accumbens ( 65 ), and substantia nigra ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of them have at least moderate histaminergic fiber density, suggesting that they are suitable for more functional research on neural circuits. In particular, VLPO, one of the most important brain nuclei that control the activity of histaminergic neurons ( 59 , 60 ), is very worthy of further research on potential closed-loop projection mechanisms. Brain histamine seems to promote motor functions overall ( 34 ), but there are still some studies that have come to different conclusions ( 61 63 ), which may be due to the different roles histamine plays in motor function in different brain regions, including globus pallidus ( 64 ), medial septal nucleus ( 39 ), nucleus accumbens ( 65 ), and substantia nigra ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently discovered that ipRGCs innervate a part of the brain preoptic area (POA) that induces NREM sleep in mice and whose neurons inhibit wakefulness-promoting brain regions 18 , 20 , 67 . In addition, another study showed that POA and tuberomammillary nucleus, structure involved in wake regulation, could operate together as a flip–flop switch that can generate transitions between waking and sleeping states 68 . Thus, a poor ipRGCs integration of the light signal, as we found in individuals with IH, could lead to a lower stimulation of the wake system and/or a lower inhibition of the brain structures involved in sleep induction.…”
Section: Discussionmentioning
confidence: 99%
“…The EEG/EMG signals were collected at a sampling rate of 128 Hz (band-pass filter EEG: 0.5–30 Hz, EMG: 20–200 Hz), amplified, and the data were stored on a local computer using Vitalrecorder software (Kissei Comtec, Nagano, Japan). The EEG/EMG data were then scored offline in consecutive 4-s epochs into three vigilance stages: awake, REM sleep, or NREM sleep (SleepSign; Kissei Comtec, Nagano, Japan), in accordance with previously established criteria ( Xu et al, 2014 ; Ren et al, 2018 ; Cheng et al, 2020 ; Li et al, 2020 ). After auto-scoring using SleepSign (Kissei Comtec), the vigilance stage data were checked, and any errors were corrected.…”
Section: Methodsmentioning
confidence: 99%